Dampak Pencemaran Lingkungan Akibat Bangkai ASF (African Swine Fever) terhadap Kesehatan Masyarakat di Kabupaten Sumba Timur - Denisius Umbu Pati; Aris U H Pari (Lembaga Pengembangan Kinerja Dosen, 2025)
African Swine Fever Virus (ASFV) is a highly contagious disease agent that causes a fatal disease in pigs, characterized by acute hemorrhagic fever. The presence of African Swine Fever (ASF) poses environmental problems. This study employed a qualitative approach with a descriptive method aimed at exploring information regarding pig carcasses resulting from ASF, community knowledge, and the impacts arising from the disposal practices of pig carcasses affected by ASF. Data were collected through interviews with informants drawn from community members and community leaders. The data collected and analyzed consisted of primary data obtained directly from respondents or informants selected based on predetermined criteria, while secondary data were used as supporting data to complement the primary data. Data analysis was conducted through the data reduction stage, which involved the process of selecting, focusing, simplifying, abstracting, and transforming raw data obtained from field notes and questionnaires. The results showed that pigs infected with ASF were predominantly in the ≥1–3 year age group, totaling 157 pigs (40.46%), while the lowest number was found in the >4 year age group, with 4 pigs (1.03%). Based on mortality categories, 298 pigs (76.80%) died due to ASF, while 90 pigs (23.19%) died from causes unrelated to ASF. The most common method of disposing of ASF-infected pigs was dumping, accounting for 206 pigs (53.09%), whereas burning was the least commonly used method, involving only 11 pigs (2.84%). The impacts of ASF incidents include significant economic losses, psychological distress among pig farmers, and environmental pollution, particularly air pollution resulting from the improper disposal of pig carcasses.